Caveolin 1 expression favors tumor growth and is associated with poor survival in primary lung adenocarcinomas - Eleonora Duregon; Rebecca Senetta; Luca Bertero; Benedetta Bussolati; Laura Annaratone; Alessandra Pittaro; Mauro Papotti; Caterina Marchiò; Paola Cassoni (Tumor Biology, 2017)
Despite the consolidated clinico-pathological correlates of Caveolin 1 expression in non–small cell lung cancer, the available data on the role of Caveolin 1 in relation to proliferation, migration, and metastasis in lung adenocarcinoma cells is still scant. Here, we aimed to confirm whether Caveolin 1 may act as a promoter of cell growth in human lung adenocarcinoma using in vitro and in vivo models, supported by a survival analysis of Caveolin 1 expression in a series of 116 primary lung adenocarcinomas. The silencing of endogenous Caveolin 1 expression in H522 lung adenocarcinoma cells through stable shRNA transfection significantly inhibited cellular proliferation in vitro and in vivo, in a lung adenocarcinoma xenograft mouse model. The bioluminescence imaging analysis revealed that tumors derived from Caveolin 1 shRNA-transfected cells grew slower than control xenografts. However, this difference progressively diminished over time and was definitively lost after 21 days. This was consistent with a progressive Caveolin 1 re-expression, which started at day 7. The association between the restored expression of Caveolin 1 and the restart of tumor growth in vivo supports the booster role of Caveolin 1 in lung adenocarcinoma progression. To further confirm this role, Caveolin 1 expression was assessed by immunohistochemistry in a series of 116 human lung adenocarcinomas. Positive Caveolin 1 tumors accounted for 20% of cases and were associated with a significantly worse overall survival compared to Caveolin 1-negative cancers. Taken together, these data highlight that Caveolin 1 expression confers a proliferative advantage in lung adenocarcinoma cells, thus fostering increased tumor aggressiveness.